Sustentabilidade hidroambiental de áreas de captações de nascentes na bacia hidrográfica do Rio Gramame-PB - Bomfim, Eudes de Oliveira (2013)
This study has aimed to determine the hydro-environmental sustainability areas s level surrounding the springs located in the Gramame basin river, Pedras de Fogo/PB. Therefore, it was necessary to develop an environmental diagnosis of the study area (around the springs); present a system of sustainability assessment for those catchment areas; determine the springs sustainability index and analyze the hydro-environmental sustainability of the areas surveyed. Four springs were chosen for the development of this research: Cacimba da Rosa e Cabelão, in the intermediate zone between urban and rural; Nova Aurora e Fazendinha, in the contryside. The methodology used to obtain the sustainability index was based on the work of the Calorie (1997) and Daniel (2000). It was used the radar chart type, by which it was possible to dynamically compare all variables. Thus, it was considered that the larger of the area in the triangle formed on the chart, greater is the indicator sustainability. The database was composed of field research, experimental analyzes, information from the springs Restoration project of the river Gramame/PB, run by the Federal University of Paraíba (UFPB), in addition to census data released by the Brazilian Institute of Geography and Statistics (IBGE). Therefore, it was elaborated a framework of indicators to assess the hydro-environmental sustainability of the areas studied. Comprise this framework twenty indicators, divided into four dimensions: social, economic, environmental and institutional. Weights were assigned 0-1 for the results obtained for each indicator. This treatment system was developed using data from a spreadsheet able to receive the data and process them automatically, converting them into indices. The final indices revealed that the area around the Nova Aurora spring got the best performances of their indicators. The methodology applied in this study stood out both for the ease of use, as the clarity in the representation of the results by measuring the condition and sustainability areas. The system of indicators used in this study should contribute to support the decision-making to improve the hydro-environmental sustainability of the springs and be reapplied to monitor the indicators performance and their indices.